Asporin repeat polymorphism in rheumatoid arthritis. Issue 1 (17th May 2006) - Torres, B; Orozco, G; García-Lozano, J R; Oliver, J; Fernández, O; González-Gay, M A; Balsa, A; García, A; Pascual-Salcedo, D; López-Nevot, M A; Núñez-Roldán, A; Martín, J; et al.
Abstract : Background: Asporin belongs to a family of proteins associated with the cartilage matrix. Objective: To investigate the role of the functional polymorphism consisting of an aspartic acid (D) repeat polymorphism located in the ASPN gene in the susceptibility to and clinical outcome of rheumatoid arthritis. Methods: A total of 803 Spanish Caucasian patients with rheumatoid arthritis and 904 controls of the same ethnic origin and matched for age and sex were included in the study. The asporin D repeat polymorphism was genotyped using polymerase chain reaction with a fluorescent primer. Results: No significant differences were detected in the distribution of the 10 alleles found in our population on comparing patients with rheumatoid arthritis with control groups. Nevertheless, individuals bearing D14 produced rheumatoid factor more often than the rest (85.7% v 72.1%, p = 0.006, odds ratio (OR)  = 2.35, 95% confidence interval 1.21 to 4.50), and the mean (SD) onset age was higher in the group of individuals bearing D13 (50.09 (13.94)) compared with the rest (47.21 (14.31)), although the difference did not reach significance (p = 0.06). Conclusion: The results do not support a major role for asporin D repeat polymorphism in the susceptibility to rheumatoid arthritis. Nevertheless, they support the influence of this gene on the outcome of the disease.